Rancang Bangun Konfigurasi Sistem Komunikasi VoIP Berbasis OpenWRT TP–Link MR–3040 dengan Antena Omnidirectional - Dina Apriyanti Simarmata; Mesra Samosir (BEES: Bulletin of Electrical and Electronics Engineering, 2020)
The development of information technology is so rapid that it makes telecommunications systems a very important thing. However, in reality there are still many areas that have not been touched and have not felt the telecommunications services, so that the community feels the impact of the difficulty to develop, both socially and economically. For this reason, a Voice over Internet Protocol (VoIP) communication system was designed. VoIP technology is implemented in a portable router and can be used as a mini Base Transceiver Station (BTS) by modifying the router with the OpenWRT operating system and omnidirectional antenna. In designing a VoIP communication system with an omnidirectional antenna, the router functions to connect between smartphones to be able to communicate via voice with Voice over Internet Protocol (VoIP) technology, and an omnidirectional antenna serves to expand the coverage area of ​​the VoIP communication system. can provide convenience to the public in communicating with a wider coverage area. In the design of VoIP communication systems with omnidirectional antennas, testing of signal quality, signal strength, and distance that can be reached from the router to the client when communicating.